An Evaluation Framework for Risk of Coastal Marine Ecological Diversity Loss From Land-Based Impacts - Hoel, Paige; Fredston, Alexa; Halpern, Benjamin S. (Frontiers in Marine Science, 2022)
Coastal environments globally are experiencing an increase in the influence and impact of human activities. Assessing the amount of modification that anthropogenic impacts cause to coastal ecosystems is imperative for characterizing and predicting habitat loss and degradation, and prioritizing conservation measures. However, as the spatial scale and data availability of coastal ecosystems vary immensely, many of the established practices on habitat risk assessment are applicable only to small scales and regions with extensive monitoring efforts. Traditional small-scale assessments also present a challenge when trying to prioritize remediation and resources over larger areas or regions. Here we show a simplified risk assessment framework, applied to a global scenario to rank the risk of loss of ecological diversity within ecoregions. Using established knowledge on sensitivities of mangroves, seagrasses, and stony corals, we create a weighted risk scoring system for each biogenic habitat. This risk score is combined with the species richness in a given ecoregion to create a priority ranking. We find that seagrass contains the largest area at severe risk of ecological diversity loss, followed by stony corals and mangroves. This work establishes a framework for assessing risk of loss of ecological diversity within ecoregions that can be used to rank the needs of the regions, from local scale applications to global scale as presented here, without extensive computing resources or exhaustive datasets.